Evaluation for an Application for iPhone and iPad: NCT Buses App - Fauzi Najim Al-Shammari, Rafeef; Mohammed Thabit A. Alsaadi, Elham (International Journal of Engineering and Technology, 2018)
NctBuses is a real time system that compute how long your bus will take to arrive for your bus stop in Nottingham city, the United Kingdom. It enables users to know when the next bus will arrive. The app counts down the minutes till your buss arrives at a particular bus stop. This paper aims to evaluate the usability and the collaboration aspects for users when they are using the app. It focuses on the main issues that facing users while utilizing this app in order to suggest recommendations to develop the usability of nctBuses in the future. The â€œField studyâ€ technique has been employed to evaluate the nctBuses Application as it is an effective method to assess the usability of such interactive systems. It helps researchers to observe the performance of users when they make use of the app. Moreover, this methodology enables researchers to have deep understanding by providing participants with a user satisfaction questionnaire. The participants that have been involved in the study are novice and expert in using the nctBuses Application. After that, the notes collected during the observation sessions have been analysed and the responses to the questionnaire have been compared. The results are analysed according to the â€œEight Golden Rules of Interface Designâ€; theory of Shneiderman and the â€œTen Usability Heuristicsâ€; theory of Nielsen. The evaluation and the analysing processes has declared the facilities of using the application. Moreover, the processes illustrate the issues in the usability of nctBuses Application. The result of the field study declares some issues that need to address in the nctbusees app to assist and enhance the software interface and performance. Â Â